38th Aerospace Sciences Meeting and Exhibit 2000
DOI: 10.2514/6.2000-868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evolving surface contamination on spacecraft charging

Abstract: The effects of evolving surface contamination on spacecraft charging have been investigated through (i) ground-based measurements of the change in electron emission properties of a conducting surface undergoing contamination and (ii) modeling of the charging of such surfaces using the NASCAP code. Specifically, we studied a Au surface as adsorbed species were removed and a very thin disordered carbon film was deposited as a result of exposure to an intense, normal incidence electron beam. As a result of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Electron emission measurements are performed in an ultra-high vacuum chamber (base pressure < 10 -9 Torr) to minimize surface contamination that can substantially affect emission properties [24], [25]. Electron sources provide electron energy ranges from ~50 eV to ~30 keV and incident electron currents (1-100 nA) with pulsing capabilities ranging from 10 ns to continuous emission [8]- [10].…”
Section: A Instrumentation and Methodsmentioning
confidence: 99%
“…Electron emission measurements are performed in an ultra-high vacuum chamber (base pressure < 10 -9 Torr) to minimize surface contamination that can substantially affect emission properties [24], [25]. Electron sources provide electron energy ranges from ~50 eV to ~30 keV and incident electron currents (1-100 nA) with pulsing capabilities ranging from 10 ns to continuous emission [8]- [10].…”
Section: A Instrumentation and Methodsmentioning
confidence: 99%
“…Fitting functions are described in. [7][8][9][10][11] Fitting parameters are listed in Table I. (b) Electron emission spectra as a function of emission energy.…”
Section: Causes Of Threshold Chargingmentioning
confidence: 99%
“…13 and 14. Fits are shown for a two parameter fit used in NASCAP 10 and a six parameter extended fit. 8,11 Fitting parameters are listed in Table I. (d) Photon-induced electron yield curves as a function of incident photon energy.…”
Section: Causes Of Threshold Chargingmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary yields is strongly dependent on the state of the material surface, which can be significantly modified due to outgassing and deposition of contaminants on the surface. 17,18 It was found that surface deposition of contaminants lead to significant decrease of γ, which reaches 50% for aluminum electrode. 17 According to Eq.…”
Section: Outgassing Induced Breakdown and Modelsmentioning
confidence: 99%